2011
DOI: 10.1159/000322824
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variant Ph Translocation t(9;22;11)(q34;q11.2;p15)inv(9)(p13q34) in Chronic Myeloid Leukemia Involving a One-Step Mechanism

Abstract: Chronic myeloid leukemia (CML) is a clonal malignant disorder of a pluripotent hematopoietic stem cell characterized by the presence of a Philadelphia (Ph) chromosome. Less than 10% of patients present variant Ph chromosomes involving 1 or more additional chromosomes, other than chromosomes 9 and 22, with uncertain prognosis. There are mainly 1- or 2-step mechanisms proposed to explain the genesis of variant Ph chromosomes depending on whether the involved chromosomes are simultaneously broken and rejoined or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…5 to 16), that is, 44.4%. Our overall rate of additional cytogenetic abnormalities is relatively high compared to that reported in the literature which is, 5 to 18% [1, 2, 4, 710]. For some there was no statistically significant difference between the future and the type of additional cytogenetic abnormalities [2, 11], for others, the difference was significant [4, 12].…”
Section: Discussioncontrasting
confidence: 43%
“…5 to 16), that is, 44.4%. Our overall rate of additional cytogenetic abnormalities is relatively high compared to that reported in the literature which is, 5 to 18% [1, 2, 4, 710]. For some there was no statistically significant difference between the future and the type of additional cytogenetic abnormalities [2, 11], for others, the difference was significant [4, 12].…”
Section: Discussioncontrasting
confidence: 43%
“…Cases of infertility and sex reversal with different translocations of chromosome 9 were reported; t(9;13), t(9;3), t(7;9), t(2;9), t(4;9), del9(p23) (12)(13)(14)(15)(16)(17) . In various leukemia patients, t(9;11) cases with different break points were observed (18,19) . Infertility cases with balanced translocations of different chromosomes were also reported (4,6,11,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported atypical t(9;22;11) translocations in CML and some have commented on the clinical course of the disease associated with the translocation. 6,7 Gahrton et al noted in 1977 that a patient was alive 10 months after diagnosis on busulfan therapy. 8 In 1985, Sessarego et al 6 described four cases of variant Philadelphia chromosome translocations in CML.…”
Section: Discussionmentioning
confidence: 99%
“…The unusual translocation did not change either the expected survival or the course of the disease. However, Belli et al 7 reported a variant translocation t(9;22;11)(q34;q11.2;p15) inv(9) (p13q34) without progression to an accelerated phase after 7 years. The present case provides a somewhat more detailed description of the clinical disease features associated with a similar translocation.…”
Section: Discussionmentioning
confidence: 99%